Targeting ADG of Developing Replacement Heifers Using Age and Body Weight - Phillip Lancaster; Cliff Lamb (EDIS, 2014)
Heifer development continues to be one of the largest expenses to cow-calf operations, primarily due to cost of feed. Replacement heifers should be bred to calve at 24 months of age in order to maximize lifetime productivity of breeding females. Therefore, heifers should conceive at 15 months of age and achieve puberty at 13–14 months of age because heifers are infertile on the pubertal estrous cycle. This 4-page fact sheet was written by Phillip Lancaster and Cliff Lamb, and published by the UF Department of Animal Sciences, September 2014.